PENGARUH INFORMASI DUNIA KERJA DAN PENGETAHUAN TENTANG ILMU KETEKNIKAN TERHADAP KESIAPAN MENJADI GURU SMK MAHASISWA SEMESTER 5 PENDIDIKAN TEKNIK MESIN FKIP UST TAHUN AKADEMIK 2015/2016 - Muhammad Zuhdi Alfian; Subagyo Subagyo (Universitas Sarjanawiyata Tamansiswa, 2017)
This aim of the research to knows: (1) Influence of world works information for being readiness teacher at vocational high school; (2) Influence of engineering knowledge for being readiness teacher at vocational high school; (3) Influence of world works information and engineering knowledge in common for being readiness teacher at vocational high school in students for 5 semester of engineering education FKIP UST for 2016/2017 periods. This research results: (1) There are positive influence and significance of word works information for being readiness teacher at vocational high school in students for 5 semester of engineering education FKIP UST for 2016/2017 periods consists 76,345% relative contributes and effective contribute 27,857%; (2) There are positive influence and significance of word works information for being readiness teacher at vocational high school in students for 5 semester of engineering education FKIP UST for 2016/2017 periods consists relative contribute 23,655%and effective contribute 8,631%; (3) There are positive influence and significance of worldworks information for engineering knowledge in common for being readiness teacher atvocational high school in students for 5 semester of engineering education FKIP UST for2016/2017 periods. The world works information for engineering knowledge in common consist relative contribute 100% and effective contribute 36,5% for being readiness teacher at vocational high school